Dynamic asymmetric impact of equity market uncertainty on energy markets: A time-varying causality analysis. (August 2022) - Hong, Yanran; Wang, Lu; Ye, Xiaoqing; Zhang, Yaojie
Abstract: This paper aims to investigate the dynamic asymmetric impact of equity market uncertainty on the energy market. For that reason, we first apply the asymmetric Granger causality test to capture both positive and negative EMV and oil shocks. We find the existence of the asymmetric effect, displaying as negative EMV shocks are the primary driving factors of positive oil shocks, while positive EMV shocks can affect negative oil shocks. Further, on the basis of three rolling-window procedures, we extend the asymmetric causality test to detect the structural breakpoints and time-varying characteristics of the causal relationships running from EMV shocks to oil shocks. Results show that some extreme events may lead to a structural breakpoint in their relationships. In particular, the negative effects of EMV shocks on oil shocks seem to be more lasting than the positive ones. Our findings may provide a new perspective on asset allocation, energy portfolio construction, and risk management. Highlights: This paper investigates the asymmetric impact of EMV shocks on crude oil shocks. We extend the asymmetric causality test based on three rolling-window procedures. The results show a significant asymmetric impact of EMV on the crude oil market. We find the structural breakpoints and time-varying characters of their causality.